Transformasi Pemikiran Islam Klasik ke Era Digital: Representasi dan Doktrin Aliran Jabbariyah dan Qadariyah di Media Sosial - Ahmad Jaya Ramadhani; Al Muzammil Bil Ilham; Abdullah Albaar (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The development of social media has transformed the way people access, understand, and disseminate religious teachings. This transformation has also revived classical Islamic theological discourses in forms that are more accessible to contemporary digital society. One of the most relevant debates concerns the doctrines of Jabariyah and Qadariyah regarding the relationship between divine will and human freedom. This study aims to analyze the representation of Jabariyah and Qadariyah doctrines on social media and their influence on digital society. The novelty of this research lies in examining the transformation of classical Islamic theological thought and its representation within the algorithm-driven ecosystem of contemporary social media. This study employs a library research method with a qualitative-descriptive approach. Data were collected from primary and secondary sources related to Islamic theology, social media, and the transformation of religious thought in the digital era. The findings reveal that Jabariyah is represented through fatalistic narratives emphasizing divine predestination, while Qadariyah is represented through motivational, productivity-oriented, and self-improvement content highlighting human agency and responsibility. These representations influence digital literacy, social behavior, learning culture, and public participation in digital spaces. Therefore, a balanced understanding between reliance on God and human effort is essential to ensure that social media is utilized constructively and responsibly.